The Dynamics Of Interstate Relations In The Caucasus A: Russian-Turkish Relations In The Post-Soviet Period - Arshakyan, Grigor M.; Safaryan, Aram V. (տպ. Atlas)
The paper examines the development of Russian-Turkish relations over the past 30 years, in the context of geopolitical relations and, in particular, the conflicts in the South Caucasus and adjacent regions. The authors consider that the two Karabakh wars, the Georgian-Abkhazian conflict and the five-day Georgian-South Ossetian war, as well as the Ukrainian crisis and the Libyan and Syrian conflicts, in which Moscow and Ankara have different interests, are the key elements in these relations. The new configuration of forces in the South Caucasus will largely depend on the outcome of these conflicts. The authors identify the main patterns in the development of Russian-Turkish bilateral relations, which are characterized by a combination of confrontation, competition and cooperation.
Keywords: History; International relations